An Utilization Of Sunlight As An Alternative Energy To Support Energy Independence In Pematang Serai Village - Zuraidah Tharo; Vina Arnita; Dwi Permatasari Barus; Jones Gultom (SEAN Institute, 2024)
The utilization of renewable energy (RE) is a crucial solution to reduce dependence on depleting fossil fuels that negatively impact the environment. One of the most promising RE sources is solar energy, given Indonesia's tropical climate and abundant sunlight. This study aims to educate and raise awareness among the community of Pematang Serai Village, Langkat Regency, about using solar energy as an environmentally friendly alternative to support energy independence. The methods applied include field observation, public education through lectures and discussions, and a simulation of a simple solar power plant (PLTS) installation. The findings indicate high community enthusiasm for understanding the concept of solar energy and its technological applications. The simulation suggested the need for three 100 Wp solar panels, four 12V 75 Ah batteries, a 1500 Watt inverter, and a 20 Ampere solar charge controller to power a 286-Watt water pump for five hours. This program successfully raised community awareness of the importance of transitioning to cleaner and more sustainable energy sources. Additionally, it aligns with the government's effort to achieve a 23% national energy mix target by 2025. With abundant solar energy potential, Pematang Serai Village has significant opportunities to become an energy-independent village through the implementation of solar power technology.